Al Emarah City Bridge, Iraq. Issue 3 (3rd July 2018) - Wang, Yingliang; Wei, Mingxia; Gao, Zongyu; Hadid, Hassoun
Abstract: This paper describes the design and construction of Al Emarah City Bridge in Iraq, which crosses the Tigris River. It includes a single-pylon cable-stayed bridge with a span distribution of 71.50 + 71.50 m, and its approach bridges on both sides are simply-supported steel–concrete girder bridges with spans of 12.25 m. The height of the pylon is 48.89 m, and the deck width is 20.00 m. The iconic pylon uses two slender steel frames connected by steel tubes in the longitudinal direction; each slender frame is elliptical in the transverse direction. The longitudinal dimension of the steel pylon is very small, so the stay cables are anchored on the outside of the pylon with a pin. The main girder is steel–concrete composite, and consists of two steel box girders, cross beams and a concrete deck slab. The anchorage between the main steel girder and the cable is located on the top flange of the girder and also uses a pin. An innovative type of cable with a double pin anchorage is used, tensioned by a temporary auxiliary device. The bridge opened to traffic at the end of 2017.